Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
1999
DOI: 10.1021/la990416u
|View full text |Cite
|
Sign up to set email alerts
|

Measuring Surface-Induced Conformational Changes in Proteins

Abstract: Microfabricated cantilever sensors were used to measure the surface stress induced by protein adsorption onto a gold surface. Two proteins, immoglobulin G (IgG) and albumin (BSA), were studied. The change of surface stress upon adsorption of IgG was found to be compressive, whereas that of BSA was tensile. This difference is elucidated in terms of protein deformation and packing. Most stress change occurs not on adsorption but over very long time scales, up to 12 h, as protein conformational changes occur. The… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
119
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 144 publications
(127 citation statements)
references
References 21 publications
7
119
0
Order By: Relevance
“…The binding of this particular antigen generated absolute tensile stress of the sensor and reference cantilever, resulting in upward bending of the cantilever spring compared with its original position. Absolute tensile deflections have been also observed previously for physical adsorption of different proteins on a gold surface of a single-cantilever array (34)(35)(36). Note that the generated surface stress is not a result of mass loaded on a cantilever but of the sum of different processes taking place at the cantilever interface, such as protein-surface and proteinprotein interactions whereby the net charge of molecular counterparts plays a key role (35).…”
Section: Resultssupporting
confidence: 65%
See 1 more Smart Citation
“…The binding of this particular antigen generated absolute tensile stress of the sensor and reference cantilever, resulting in upward bending of the cantilever spring compared with its original position. Absolute tensile deflections have been also observed previously for physical adsorption of different proteins on a gold surface of a single-cantilever array (34)(35)(36). Note that the generated surface stress is not a result of mass loaded on a cantilever but of the sum of different processes taking place at the cantilever interface, such as protein-surface and proteinprotein interactions whereby the net charge of molecular counterparts plays a key role (35).…”
Section: Resultssupporting
confidence: 65%
“…Absolute tensile deflections have been also observed previously for physical adsorption of different proteins on a gold surface of a single-cantilever array (34)(35)(36). Note that the generated surface stress is not a result of mass loaded on a cantilever but of the sum of different processes taking place at the cantilever interface, such as protein-surface and proteinprotein interactions whereby the net charge of molecular counterparts plays a key role (35). Therefore, even though the surface is becoming more crowded, changes in surface charge and hydrophilicity of molecules upon formation of antibody-antigen complex result in a tensile stress with an upward movement.…”
Section: Resultssupporting
confidence: 65%
“…Each step gives rise to an increased number of interaction points between the protein and the surface and between the adsorbed proteins themselves. [26] "Hard" proteins, on the other hand, such as lysozyme are more resistant to major changes. [27] The early example of protein conformational changes upon adsorption to polymer surface has been reported by Soria et al [28] The authors showed that, contrary to native protein in blood, adsorbed fibrinogen exposes D-domain which binds the monoclonal antibody.…”
Section: Adsorption Influenced By Protein Molecular Propertiesmentioning
confidence: 99%
“…Typical dimensions of a microcantilever, which are similar to AFM probes, are 200 μm long, 1 μm thick, and 20 μm wide (Goeders et al, 2008;Lavrik et al, 2004). The microcantilever is capable of detecting minute changes in interaction energy between individual molecules in the thin film of a polymer coating (cellulose, protein, DNA, or polymer brush) in the form of a measurable bending (10 -6 to 10 -12 m) of the microcantilever (Moulin et al, 1999;Mukhopadhyay et al, 2005;Shu et al, 2005;Yan et al, 2006;Zhao et al, 2010;Zhou et al, 2006). The microcantilever bending can be measured based on the deflection of a laser beam reflecting from the tip of the microcantilever in the AFM (Figure 9).…”
Section: Microcantilever and Its Applicationsmentioning
confidence: 99%